Juvenile idiopathic arthritis polygenic risk scores are associated with cardiovascular phenotypes in early adulthood: a phenome-wide association study - Sarah L. N. Clarke; Hannah J. Jones; Gemma C. Sharp; Kayleigh E. Easey; Alun D. Hughes; Athimalaipet V. Ramanan; Caroline L. Relton (BMC, 2022)
Abstract Background There is growing concern about the long-term cardiovascular health of patients with juvenile idiopathic arthritis (JIA). In this study we assessed the association between JIA polygenic risk and cardiovascular phenotypes (cardiovascular risk factors, early atherosclerosis/arteriosclerosis markers, and cardiac structure and function measures) early in life. Methods JIA polygenic risk scores (PRSs) were constructed for 2,815 participants from the Avon Longitudinal Study of Parents and Children, using the single nucleotide polymorphism (SNP) weights from the most recent JIA genome wide association study. The association between JIA PRSs and cardiovascular phenotypes at age 24 years was assessed using linear and logistic regression. For outcomes with strong evidence of association, further analysis was undertaken to examine how early in life (from age seven onwards) these associations manifest. Results The JIA PRS was associated with diastolic blood pressure (β 0.062, 95% CI 0.026 to 0.099, P = 0.001), insulin (β 0.050, 95% CI 0.011 to 0.090, P = 0.013), insulin resistance index (HOMA2_IR, β 0.054, 95% CI 0.014 to 0.095, P = 0.009), log hsCRP (β 0.053, 95% CI 0.011 to 0.095, P = 0.014), waist circumference (β 0.041, 95% CI 0.007 to 0.075, P = 0.017), fat mass index (β 0.049, 95% CI 0.016 to 0.083, P = 0.004) and body mass index (β 0.046, 95% CI 0.011 to 0.081, P = 0.010). For anthropometric measures and diastolic blood pressure, there was suggestive evidence of association with JIA PRS from age seven years. The findings were consistent across multiple sensitivity analyses. Conclusions Genetic liability to JIA is associated with multiple cardiovascular risk factors, supporting the hypothesis of increased cardiovascular risk in JIA. Our findings suggest that cardiovascular risk is a core feature of JIA, rather than secondary to the disease activity/treatment, and that cardiovascular risk counselling should form part of patient care.